ECO-WAVE MAG: Inovasi Teknologi Pengeringan Maggot Berbasis Circular Economy pada Mitra (Black Soldier Fly) BSF Ratna Medan: Pengabdian - Hasibuan, Gina Cynthia Raphita; Fath, Muhammad Thoriq Al; Sidabutar, Rivaldi; Ginting, Muhammad Hendra Sahputra; Angel, Angel; Nasution, Dea Amanda Sari; Catherine, Ester Sara; Nasution, Juan Akmal; Alamsyah, Vandria; Fajar, Muhammad (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The increase in organic waste generation in Indonesia is driving the need for more sustainable waste management innovations, including through the bioconversion of maggots as an alternative protein source. However, at a business scale like Ratna's Black Soldier Fly (BSF), the maggot drying process remains a major obstacle because conventional methods produce inconsistent quality, require long drying times, and are energy-intensive. A community service project titled ECO-WAVE MAG was introduced to address this issue by implementing a microwave dryer as an appropriate technology. Activities included field surveys, designing and modifying the drying system, technical testing on fresh maggots with a moisture content of around 70 percent, and providing training and operational assistance to partners. Test results showed that the microwave dryer was able to reduce drying time by up to 70 percent, produce a stable final moisture content of 8–10 percent, and maintain the homogeneity and nutritional quality of the dried maggots. This technology also proved to be more energy efficient and able to increase production capacity and product shelf life.